Does electrical stimulation enhance post-exercise performance recovery? - Babault, N.; Cometti, C.; Maffiuletti, N. A.; Deley, G. (European Journal of Applied Physiology, 2011)
Elite sport requires high-volume and high-intensity training that inevitably induces neuromuscular fatigue detrimental for physical performance. Improving recovery processes is, therefore, fundamental and to this, a wide variety of recovery modalities could be proposed. Among them, neuromuscular electrical stimulation is largely adopted particularly by endurance-type and team sport athletes. This type of solicitation, when used with low stimulation frequencies, induces contractions of short duration and low intensity comparable to active recovery. This might be of interest to favour muscle blood flow and therefore metabolites washout to accelerate recovery kinetics during and after fatiguing exercises, training sessions or competition. However, although electrical stimulation is often used for recovery, limited evidence exists regarding its effects for an improvement of most physiological variables or reduced subjective rating of muscle soreness. Therefore, the main aim of this brief review is to present recent results from the literature to clarify the effectiveness of electrical stimulation as a recovery modality.